2013
DOI: 10.1021/ja4049114
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Aqueous Suzuki–Miyaura Coupling Allows Site-Specific Polypeptide 18F-Labeling

Abstract: The excesses of reagents used in protein chemistry are often incompatible with the reduced or even inverse stoichiometries used for efficient radiolabeling. Analysis and screening of aqueous Pd(0) ligand systems has revealed the importance of a guanidine core and the discovery of 1,1-dimethylguanidine as an enhanced ligand for aqueous Suzuki–Miyaura cross-coupling. This novel Pd catalyst system has now allowed the labeling of small molecules, peptides, and proteins with the fluorine-18 prosthetic [18F]4-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 42 publications
1
104
0
7
Order By: Relevance
“…5a), while the minimal motif guanidine-based ligands (L3 and L4 in Fig. 5a) can significantly enhance the rate of Suzuki reactions relative to ADHP 128 and allow efficient couplings even at low stoichiometries and concentrations suitable when labelling with scarce reagents 129 . It was also shown that PEG chains offer new reactivity and a significant enhancement in rate as self-liganding (internally chelating) boronic acids when used with Pd(OAc) 2 to give a high-yielding site-specific PEGylation of proteins 128 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…5a), while the minimal motif guanidine-based ligands (L3 and L4 in Fig. 5a) can significantly enhance the rate of Suzuki reactions relative to ADHP 128 and allow efficient couplings even at low stoichiometries and concentrations suitable when labelling with scarce reagents 129 . It was also shown that PEG chains offer new reactivity and a significant enhancement in rate as self-liganding (internally chelating) boronic acids when used with Pd(OAc) 2 to give a high-yielding site-specific PEGylation of proteins 128 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…In the field of homogenous Pd-mediated chemistry, Davis developed biomolecule compatible Pd-complexes and strategies to tag and modify peptides, sugars [19], proteins [20,21 ] and DNA [23]. Davis elegantly exemplified the in vitro labelling of biomolecules by incorporation of various chemical tags by chemical (e.g.…”
Section: Homogenous Pd-mediated Chemistrymentioning
confidence: 99%
“…For example, 3,3′,3″-phosphanetriyltris(benzene sulfonic acid) trisodium salt (TPPTS 77a, Figure 12) [18,64], its xylene analogue TXPTS 77b [64,133], sodium 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl-3'-sulfonate (SSPhos 78) [10,96], and water-soluble NHC-ligands (N-heterocyclic carbene), such as 79 [134][135][136][137], have been proposed for Pd-catalysis in aqueous media (Figure 12). Suzuki-Miyaura reactions encompassing other water soluble ligands [11,12,138], or additives such as polyethyleneglycol and surfactants were also applied [11,34,139] Notably for Suzuki-Miyaura reaction in aqueous conditions, ligands containing the guanidine functionality, such as 2-aminopyrimidine-4,6-diol disodium salt (ADHP 80a) [63,140], its dimethylated analogue (N,N-diMeADHP 80b) [34], and (methyl)guanidines 81 and 82 [34,141,142], have been reported. The development of peptide diversification through Suzuki-Miyaura reactions in a purely aqueous environment was first reported by Vilaró et al [143].…”
Section: Suzuki-miyaura Reaction On Peptidic Substratesmentioning
confidence: 99%
“…Converting these findings on the iodinated proteins showed that these "self-liganded" conditions resulted in high conversion for both Npβ-69pIPhe and SBL-156Pic with respectively 40 and 10 eq of Pd catalyst and 1000 eq of the mPEG 2k -PBA ( Figure 17C). Application of the guanidine-based ligands was furthermore explored for the introduction of 18 F tags by Gao et al [142]. With 1,1-dimethylguanidine 82 as a ligand, the first Pd-catalyzed introduction of 18 F, the most common radionuclide in PET imaging, was exemplified on SBL-156Pic ( Figure 17D) with 250 eq of Pd-catalyst solution and 250 eq of labeled 4-fluorophenylboronic acid.…”
Section: Protein Derivatizationmentioning
confidence: 99%